2006
DOI: 10.1177/1524839906289583
|View full text |Cite
|
Sign up to set email alerts
|

State Health Policy Makers: What’s the Message and Who’s Listening?

Abstract: This article is based on a white paper commissioned by the Directors of Health Promotion and Education, a national organization representing state health agency directors and practitioners in health promotion and education initiatives. The work reflects an assessment of current understanding of how state-level policy makers receive and use information related to health promotion and chronic disease prevention. Although health education practitioners are routinely encouraged to use policy and environmental chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…To do this, researchers must involve end users, policymakers, and transdisciplinary teams from the earliest stages of the design process (Jones, Kreuter, Pritchett, Matulionis, & Hann, 2006;Kessler & Glasgow, 2011;Ross, Lavis, Rosriguez, Woodside, & Denis, 2003). (2) Move beyond direct replication of efficacy randomized controlled trials (RCTs): Use alternatives such as replication across varied settings and conditions, effectiveness and dissemination studies, cohort multiple RCT designs, quasi-experimental designs, and studies based in rapidlearning, real-world settings such as health-maintenance organizations, public healthcare systems, primary care-based networks, education systems, etc.…”
Section: Shift Priorities In Research Designs and Methodsmentioning
confidence: 99%
“…To do this, researchers must involve end users, policymakers, and transdisciplinary teams from the earliest stages of the design process (Jones, Kreuter, Pritchett, Matulionis, & Hann, 2006;Kessler & Glasgow, 2011;Ross, Lavis, Rosriguez, Woodside, & Denis, 2003). (2) Move beyond direct replication of efficacy randomized controlled trials (RCTs): Use alternatives such as replication across varied settings and conditions, effectiveness and dissemination studies, cohort multiple RCT designs, quasi-experimental designs, and studies based in rapidlearning, real-world settings such as health-maintenance organizations, public healthcare systems, primary care-based networks, education systems, etc.…”
Section: Shift Priorities In Research Designs and Methodsmentioning
confidence: 99%
“…A common critique of policy practices by researchers is the failure to integrate scientific evidence into the decision-making process, while policy makers often call into question the usefulness of research findings and policy recommendations that are put forth by researchers [12,13]. At the same time, it has been observed that research findings are not generally targeted to policy makers; the questions that researchers seek to answer are often quite different than those facing policy makers, even though they may address the same subject matter [14].…”
Section: The Research-policy Interactionmentioning
confidence: 99%
“…These references suggest that while research evidence, whether it is published in scientific journals or solicited from researchers themselves, is included among the sources of evidence used by policy makers, it is one of many sources. As such, there is a need for researchers to pro-actively market their research findings to policy makers by establishing direct relationships with policy makers or through partnerships with advocates [12].…”
Section: The Research-policy Interactionmentioning
confidence: 99%
“…evidence becomes more relevant to policy makers when it involves a local example and when the effects are framed in terms of its direct impact on one's local community, family, or constituents. 26 in the policy arena, decision makers indicate that relevance to current debates is a critical factor in determining which research will be used and which proposals will be considered. 27 Research on contextual issues and the importance of narrative communication is beginning to present data in the form of a story that helps to personalize an issue.…”
Section: Implications For Practitionersmentioning
confidence: 99%
“…Getting to know their preferences can also help tailor information to their needs. 26 building these connections can help facilitate "champions" for the cause. 29,30 • Learn from successful efforts and apply effective strategies.…”
Section: Implications For Practitionersmentioning
confidence: 99%